DISKURSUS GENDER DALAM PANDANGAN NASR HAMID ABU ZAYD (LP2M IAIN Jember (now UIN Kiai Haji Achmad Siddiq Jember), 2013)
Departing from the assumption that one of the causes of social inequality is a misconception on the view of relation between men and women. This assumption is then developed into a social analysis, namely the gender analysis. The results of gender analysis were quite surprising and raise pro and contra. This is due to this tool of analysis is used to read religious texts that have been considered settle ,final and can no longer be contested. Nasr Hamid Abu Zayd, as a contemporary Muslim thinker trying to perform ijtihad by conducting critical rereading of the discourse and religious texts as well as texts relating to women. In the gender analysis, the religious texts are constructed in accordance with the character and social situation at the time the text was produced. The book of Dawair al-Khauf, Qiraat fi Khitab al-Mar’ah, the work of Nasr Hamid Abu Zayd which is discussed in this paper, become an evidence that Abu Zayd deserves to be called as a true feminist. In this book he offers a model of contextual readings (manhaj al-qiraah as-siyaqiyah) in understanding the religious texts, especially the Qur'an and the Hadith. This method see the problem from a broader perspective, the overall social context of historical revelation to understand the meaning of the text. This contextual readings also make a distinction between the historical meaning derived from a context on one side, and the significance (al-magza) which are indicated by the meaning in the context of the socio-historical interpretation on the other side. This method is then used by Nasr Hamid Abu Zayd in exploring the understanding of the text of the Qur'an and Hadith, especially with regard to the gender relations in relation to the issues of qawwamah, polygamy and divorce, inheritance issues and problems of aurat and hijab.